Ebola outbreak and investigational drug controversy - Chary, Krishnan Venadaragava (International Journal of Research in Medical Sciences, 2017)
In 2014, first announcement on Ebola virus epidemic was made on 25 March by the World Health Organisation (WHO). Infection occurred in four southern regions of guinea, 86 people were infected and 69 people died of Ebola. This epidemic was caused by Zaire strain and infection was spreading rapidly, by March 31 2014 another 16 cases reported to the WHO.